The effectiveness of compensation structures in reducing turnover among employees at NXP Semiconductor Sdn. Bhd. / Juita Razinoor Johar - Johar, Juita Razinoor (Faculty of Business and Management, 2012)
Background: Employee turnover is a normal situation that occurs in the company. However, if this phenomenon is continuously happen, it will affect company’s productivity. Retaining employees in the company is a big challenge for the management levels. Therefore, management in the company needs to identify the best solution to control the rate of employee turnover.